PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN APLIKASI SMART APP CREATOR 3 PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Ali, Jihan; Annisa, Annisa; Wasid, Ahmad; Rahmadani, Kurniati; Fricticarani, Ade; Dayurni, Popi (Information Technology Education Department, 2024)
The use of learning media is an integral part of the learning method used. This study aims to develop Smart App Creator 3 learning media in Information and Communication Technology subjects. The research method used is the R&D method with data collection techniques through a questionnaire given to 17 class X students of SMK Pasundan 1 Serang City. The results of the study were valid learning media with a value of 0.875. Practicality test of learning media given to 1 teacher and 1 lecturer with an average percentage of 83.6%. While the results obtained from the analysis of practicality by students are an average percentage of 82.35%. So it can be concluded that Smart App Creator 3 learning media is feasible to use as learning media. This research is expected to be a learning media for Information and Communication Technology subjects and can be useful for teachers, students and advanced researchers.